2021
DOI: 10.31764/jpmb.v5i1.5583
|View full text |Cite
|
Sign up to set email alerts
|

Edukasi Masyarakat Peduli Air Bersih Dalam Upaya Peningkatan Pengetahuan Masyarakat Tentang Cara Pengelolaan Air Minum Di Desa Pemurus Rt 3b Kecamatan Aluh-Aluh Berbasis Daring

Abstract: ABSTRAKAir merupakan kebutuhan bagi setiap kehidupan, semua makhluk hidup memerlukan air dalam kehidupannnya sehingga tanpa air dapat dipastikan tidak akan ada kehidupan. Sebagian besar masyarakat yang mengalami kesulitan memperoleh air bersih untuk digunakan sebagai air minum tersebut adalah masyarakat yang tinggal di perdesaan. Kegiatan ini bertujuan untuk meningkatkan pengetahuan dan sikap masyarakat tentang cara pengelolaan air minum di Desa Pemurus RT.3B Kecamatan Aluh-Aluh. Sasaran kegiatan ini adalah ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Table 1 shows data from the Pre-Test and Post-Test findings that were assessed using the Wilcoxon test analysis because the data were not normally distributed. (Hildawati et al, 2021). Another study found variations in food and beverage sanitation hygiene knowledge and practice before and after counseling (Ningsih, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows data from the Pre-Test and Post-Test findings that were assessed using the Wilcoxon test analysis because the data were not normally distributed. (Hildawati et al, 2021). Another study found variations in food and beverage sanitation hygiene knowledge and practice before and after counseling (Ningsih, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…conducted by Hildawati et al (2021) in Pemurus Village shows that good knowledge influences behaviour in drinking water treatment. Research result in Duan et al (2022), Drinking water perceptions, health literacy, economic and cultural levels, and drinking water consumption behaviour are important factors that influence the willingness of middle-aged and elderly residents to drink unboiled and filtered tap water.…”
Section: Relationship Between Education Level and Knowledge About The...mentioning
confidence: 99%
“…Hasil ini sesuai dengan penelitian Hildawati (2021) yang menunjukkan adanya perbedaan hasil pre-test dan post-test pengetahuan sebelum dan sesudah dilakukan penyuluhan terkait cara pengelolaan air minum di desa (Hildawati et al, 2021). Penelitian lain juga menyebutkana bahwa terdapat perbedaan pengetahuan dan praktik hygiene sanitasi makanan dan minuman sebelum dan sesudah penyuluhan (Ningsih, 2014).…”
Section: Hasil Dan Diskusiunclassified